Digital Leadership and Organizational Citizenship Behavior in Healthcare Organizations: A Conceptual Perspective - Teguh Setiawan Wibowo; Christina Wulansari (MAPAN: Jurnal Manajemen Akuntansi Palapa Nusantara, 2026)
The rapid digital transformation of healthcare organizations has created unprecedented challenges for employees, including technostress, work overload, and resistance to change, while simultaneously demanding discretionary extra-role behaviors known as organizational citizenship behavior (OCB). This conceptual paper aims to develop a comprehensive theoretical framework explaining the relationship between digital leadership and OCB in healthcare organizations. Drawing upon Job Demands-Resources (JD-R) theory and Social Exchange Theory (SET), the paper proposes that work engagement mediates the positive relationship between digital leadership and OCB, while technostress moderates the digital leadership–work engagement relationship. The framework advances four key propositions: (H1) digital leadership positively influences work engagement; (H2) work engagement positively influences OCB; (H3) work engagement mediates the digital leadership–OCB relationship; and (H4) technostress weakens the positive effect of digital leadership on work engagement. The paper makes three theoretical contributions: extending JD-R theory by conceptualizing digital leadership as a critical job resource and technostress as a boundary condition; integrating leadership, technostress, engagement, and OCB into a unified moderated mediation model; and addressing the underexplored healthcare context. Practical implications suggest that healthcare organizations should develop digital leadership competencies while simultaneously mitigating technostress through adequate training, technical support, and user-friendly system design. Future research directions include empirical testing using SEM-PLS, longitudinal designs, mixed methods, and multilevel analysis across diverse healthcare settings such as hospitals, nurses, pharmacists, and public health workers.